Physiological Roles of Flavodiiron Proteins and Photorespiration in the Liverwort Marchantia polymorpha - Shimakawa, Ginga; Hanawa, Hitomi; Wada, Shinya; Hanke, Guy T.; Matsuda, Yusuke; Miyake, Chikahiro (Frontiers in Plant Science, 2021)
Against the potential risk in oxygenic photosynthesis, that is, the generation of reactive oxygen species, photosynthetic electron transport needs to be regulated in response to environmental fluctuations. One of the most important regulations is keeping the reaction center chlorophyll (P700) of photosystem I (PSI) in its oxidized form in excess light conditions. The oxidation of P700 is supported by dissipating excess electrons safely to O2, and we previously found that the molecular mechanism of the alternative electron sink is changed from flavodiiron proteins (FLV) to photorespiration in the evolutionary history from cyanobacteria to plants. However, the overall picture of the regulation of photosynthetic electron transport is still not clear in bryophytes, the evolutionary intermediates. Here, we investigated the physiological roles of FLV and photorespiration for P700 oxidation in the liverwort Marchantia polymorpha by using the mutants deficient in FLV (flv1) at different O2 partial pressures. The effective quantum yield of photosystem II significantly decreased at 2 kPa O2 in flv1, indicating that photorespiration functions as the electron sink. Nevertheless, it was clear from the phenotype of flv1 that FLV was dominant for P700 oxidation in M. polymorpha. These data suggested that photorespiration has yet not replaced FLV in functioning for P700 oxidation in the basal land plant probably because of the lower contribution to lumen acidification, compared with FLV, as reflected in the results of electrochromic shift analysis.